2010
DOI: 10.1152/ajpendo.00417.2009
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 inhibits inflammatory pathways in macrophages and modulates insulin sensitivity

Abstract: padhyay G, Olefsky JM. SIRT1 inhibits inflammatory pathways in macrophages and modulates insulin sensitivity. Am J Physiol Endocrinol Metab 298: E419 -E428, 2010. First published December 8, 2009; doi:10.1152/ajpendo.00417.2009.-Chronic inflammation is an important etiology underlying obesity-related disorders such as insulin resistance and type 2 diabetes, and recent findings indicate that the macrophage can be the initiating cell type responsible for this chronic inflammatory state. The mammalian silent info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
294
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(321 citation statements)
references
References 40 publications
14
294
2
1
Order By: Relevance
“…The results presented here show that SIRT1 represses LEF1 gene expression, which activates MMP13 gene expression. Studies have shown that SIRT1 can demonstrate a broad antiinflammatory function in a variety of tissues (44)(45)(46)(47)(48)(49). For example, in chronic obstructive pulmonary disorder, SIRT1 exerts a protective effect, partially because of its capacity to down-regulate MMP9 (49), and modulating NFkB activity during the disease (48).…”
Section: Sirt1 Represses Mmp13 Gene Expression 3123mentioning
confidence: 99%
“…The results presented here show that SIRT1 represses LEF1 gene expression, which activates MMP13 gene expression. Studies have shown that SIRT1 can demonstrate a broad antiinflammatory function in a variety of tissues (44)(45)(46)(47)(48)(49). For example, in chronic obstructive pulmonary disorder, SIRT1 exerts a protective effect, partially because of its capacity to down-regulate MMP9 (49), and modulating NFkB activity during the disease (48).…”
Section: Sirt1 Represses Mmp13 Gene Expression 3123mentioning
confidence: 99%
“…Similar to PARP-2 gene inactivation, SIRT1 activation has been shown to inhibit the production of inflammatory mediators and suppress certain forms of inflammation [92][93][94]. It is therefore plausible that the induction of SIRT1 may be responsible for the antiinflammatory effect of PARP-2 depletion in colitis [59] and in astrocyte activation [58] .…”
Section: Interaction With Sirt1mentioning
confidence: 99%
“…In skeletal muscle cells, PPAR/ agonism inhibited palmitate-induced ER stress and significantly decreased levels of pro-inflammatory cytokines, TNF and IL-6, in an AMPK dependent manner [90]. The inflammatory environment in T2DM could be abrogated by increased activity of PPAR/ target genes such as SIRT1 [91,92].…”
Section: Proteotoxic Stress In the Pathogenesis Of Diseases Not Formementioning
confidence: 99%